INTERAKSI ORANG TUA DALAM MENGEMBANGKAN KEMAMPUAN MENGENAL LAMBANG BILANGAN SELAMA MASA PANDEMI COVID-19 PADA ANAK KELOMPOK A2 DI TK MUSLIMAT NU 18 MALANG - Diah Khikmatul Indayani; Mohammad Afifulloh; Ika Anggraheni (UNISMA, 2022)
During this current pandemic situation, having activities in school was not allowed and changed into the online class system. Parents' can now keep an eye on their children more frequent because their children is always at home. This study tries to figure out the interaction between parents and their children, the children's ability to recognize the number and symbol during pandemic, and the correlation between those two. This study took place in TK Muslimat NU 18 Malang, specifically the students of A2 group. This research is utilizing qualitative approach. In order to collect the data, several data gathering techniques such as interview, observation, and documentation are employed in this study. The study found that all of respondents are able to handle their children's learning activities despite of the democratic parenting styles. The teaching method used was also well-applied to each of their children. The parents' accompaniment intensity was considered as high.